PEMANFAATAN INTERNET UNTUK MEMPERBAHARUI MODEL PENGAJARAN DI PERGURUAN TINGGI - Herman Dwi Surjo~lo, Herman Dwi Surjo~lo (Jurnal Cakrawala Pendidikan, 2016)
The widespread acceptance of the inteniet and more specifically the World Wide Web (WWW) has raised the awareness of educators to the potential for on-line education and virtual university. The web as a new phenomenon in the info~~natiolnan dscape of the university is used to support course instruction. An innovati\e model of webbased university instruction is presented that more fully expresses and uses the power of the web in opening up [lie interaction between student and knowledge.